Abel im Dialog : Perspektiven der Zeichen- und Interpretationsphilosophie - Dirks, Ulrich; Wagner, Astrid (De Gruyter, 2018)
Perception, speech, thought, and action are symbolic and interpretative processes. Their understanding motivates Günter Abel's general philosophy of signs and interpretation. Philosophers and other scholars engage in dialogue with Abel on the essential features, hypotheses, and arguments of his thought. The dialogues reveal the potential relevance of his ideas for natural science, politics, the law, architecture, technology, the arts, and music.